A new staining protocol for detection of murine antibody-secreting plasma cell subsets by flow cytometry - Pracht, Katharina; Meinzinger, Julia; Daum, Patrick; Schulz, Sebastian; Reimer, Dorothea; Hauke, Manuela; Roth, Edith; Mielenz, Dirk; Berek, Claudia; Corte-Real, Joana; Jäck, Hans-Martin; Schuh, Wolfgang (European Journal of Immunology, 2017)
We provide a robust four-color fluorescence-based flow cytometry protocol that distinguishes viable dividing plasmablasts from nondividing plasma cells and, based on CD19 surface abundance, identifies two mature plasma cell populations in the spleen and the bone marrow of mice.
EVALuna2:13650

Augmented neutralization of SARS-CoV-2 Omicron variant by boost vaccination and monoclonal antibodies - Schulz, Sebastian; Hoffmann, Markus; Roth, Edith; Pracht, Katharina; Burnett, Deborah L.; Mazigi, Ohan; Schuh, Wolfgang; Manger, Bernhard; Mielenz, Dirk; Goodnow, Christopher C.; Christ, Daniel; Poehlmann, Stefan; et al. (European Journal of Immunology, 2022)
Effective vaccines and monoclonal antibodies have been developed against coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, the appearance of virus variants with higher transmissibility and pathogenicity is a major concern because of their potential to escape vaccines and clinically approved SARS-CoV-2- antibodies. Here, we use flow cytometry-based binding and pseudotyped SARS-CoV-2 neutralization assays to determine the efficacy of boost immunization and therapeutic antibodies to neutralize the dominant Omicron variant. We provide compelling evidence that the third vaccination with BNT162b2 increases the amount of neutralizing serum antibodies against Delta and Omicron variants, albeit to a lower degree when compared to the parental Wuhan strain. Therefore, a third vaccination is warranted to increase titers of protective serum antibodies, especially in the case of the Omicron variant. We also found that most clinically approved and otherwise potent therapeutic antibodies against the Delta variant failed to recognize and neutralize the Omicron variant. In contrast, some antibodies under preclinical development potentially neutralized the Omicron variant. Our studies also support using a flow cytometry-based antibody binding assay to rapidly monitor therapeutic candidates and serum titers against emerging SARS-CoV-2 variants.
CRIS-Team WoS Importer:2022-04-08

Decoding plasma cell maturation dynamics with BCMA - Schulz, Sebastian; Menzel, Shannon; Wittner, Jens; Ulbricht, Carolin; Grofe, Alina T.; Roth, Edith; Mann-Nüttel, Ritu; Scheu, Stefanie; Kueh, Andrew J.; Jäck, Alexander; Herold, Marco J.; Hauser, Anja E.; et al. (Frontiers in Immunology, 2025)
Plasma cells provide protective antibodies following an infection or vaccination. A network of intrinsic and extrinsic factors fine-tunes the generation of a heterogenous plasma cell pool with varying metabolic requirements, transcriptional profiles and lifespans. Among these, the B cell maturation antigen (BCMA) has been implicated in the APRIL-mediated survival of long-lived plasma cells. To characterize the terminal maturation of plasma cells, we constructed a BCMA reporter mouse (BCMA:Tom) that exclusively labeled antibody-secreting cells and revealed that BCMA:Tom expression varied by IgH isotype and increased with plasma cell maturity. The BCMA reporter, used alongside the Blimp1-GFP reporter, also allowed detailed tracking of plasma cell development and highlighted the importance of the in vivo microenvironment to complete plasma cell maturation. Therefore, the BCMA:Tom reporter mouse provides a valuable tool for tracking plasma cell development and maturation with flow cytometry or advanced imaging techniques, enabling a deeper understanding of the mechanisms regulating plasma cell heterogeneity and longevity.
CRIS-Team Scopus Importer:2025-04-01
Keywords: antibody-secreting cells (ASC); BCMA (TNFRSF17); bone marrow; plasma cells; spleen; survival; thymus

Deficiency of the microprocessor component DGCR8 impairs macrophage growth and unleashes IFN-dependent gene expression in response to mycobacteria - Killy, Barbara; Bodendorfer, B.; Pracht, Katharina; Jäck, Hans-Martin; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

DGCR8 deficiency impairs macrophage growth and unleashes the interferon response to mycobacteria - Killy, Barbara; Bodendorfer, Barbara; Mages, Jörg; Ritter, Kristina; Schreiber, Jonathan; Hölscher, Christoph; Pracht, Katharina; Ekici, Arif Bülent; Jäck, Hans-Martin; Lang, Roland (Life Science Alliance, 2021)
The mycobacterial cell wall glycolipid trehalose-6,6-dimycolate (TDM) activates macrophages through the C-type lectin receptor MINCLE. Regulation of innate immune cells relies on miRNAs, which may be exploited by mycobacteria to survive and replicate in macrophages. Here, we have used macrophages deficient in the microprocessor component DGCR8 to investigate the impact of miRNA on the response to TDM. Deletion of DGCR8 in bone marrow progenitors reduced macrophage yield, but did not block macrophage differentiation. DGCR8-deficient macrophages showed reduced constitutive and TDM-inducible miRNA expression. RNAseq analysis revealed that they accumulated primary miRNA transcripts and displayed a modest type I IFN signature at baseline. Stimulation with TDM in the absence of DGCR8 induced overshooting expression of IFNβ and IFN-induced genes, which was blocked by antibodies to type I IFN. In contrast, signaling and transcriptional responses to recombinant IFNβ were unaltered. Infection with live Mycobacterium bovis Bacille Calmette-Guerin replicated the enhanced IFN response. Together, our results reveal an essential role for DGCR8 in curbing IFNβ expression macrophage reprogramming by mycobacteria.
CRIS-Team Scopus Importer:2021-04-16

Eosinophils are not essential for maintenance of murine plasma cells in the bone marrow - Haberland, Konrad; Ackermann, Jochen A.; Ipseiz, Natacha; Culemann, Stephan; Pracht, Katharina; Englbrecht, Matthias; Jäck, Hans-Martin; Schett, Georg; Schuh, Wolfgang; Krönke, Gerhard (European Journal of Immunology, 2018)
Eosinophils were reported to serve as an essential component of the plasma cell niche within the bone marrow. As the potential contribution of eosinophils to humoral immunity has remained incompletely understood, we aimed to further characterize their role during antibody responses and to additionally investigate their role in autoimmune disease. Contrary to our expectations and the currently prevailing paradigm, we found that eosinophils are fully dispensable for the survival of murine bone marrow plasma cells and accordingly do not contribute to antibody production and autoantibody-mediated disease. Littermate wild type and eosinophil-deficient ΔdblGATA-1 animals showed similar numbers and frequencies of plasma cells and did not differ in steady state levels of immunoglobulins or their ability to raise antigen-specific antibody responses. Eosinophils were likewise dispensable for autoantibody production or autoantibody-induced disease in a mouse model of systemic lupus erythematosus. Our findings thus argue against a role of eosinophils during the maintenance of the plasma cell pool and challenge the hitherto postulated concept of an eosinophil-sustained bone marrow niche.
EVALuna2:34472

Glucose transporter type 1: metabolic player in antibody-secreting plasma cells - Bierling, Theresa; Gumann, A.; Van Schie, K.; Wittner, Jens; Wichert, M.; Hauke, Manuela; Toes, R. E.; Mielenz, Dirk; Jäck, Hans-Martin; Pracht, Katharina (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

GLUT1-mediated glucose import in B cells is critical for anaplerotic balance and humoral immunity - Bierling, Theresa; Gumann, Amelie; Ottmann, Shannon; Schulz, Sebastian; Weckwerth, Leonie; Thomas, Jana; Geßner, Arne; Wichert, Magdalena; Kuwert, Frederic; Rost, Franziska; Hauke, Manuela; Freudenreich, Tatjana; et al. (Cell Reports, 2024)
Glucose uptake increases during B cell activation and antibody-secreting cell (ASC) differentiation, but conflicting findings prevent a clear metabolic profile at different stages of B cell activation. Deletion of the glucose transporter type 1 (GLUT1) gene in mature B cells (GLUT1-cKO) results in normal B cell development, but it reduces germinal center B cells and ASCs. GLUT1-cKO mice show decreased antigen-specific antibody titers after vaccination. In vitro, GLUT1-deficient B cells show impaired activation, whereas established plasmablasts abolish glycolysis, relying on mitochondrial activity and fatty acids. Transcriptomics and metabolomics reveal an altered anaplerotic balance in GLUT1-deficient ASCs. Despite attempts to compensate for glucose deprivation by increasing mitochondrial mass and gene expression associated with glycolysis, the tricarboxylic acid cycle, and hexosamine synthesis, GLUT1-deficient ASCs lack the metabolites for energy production and mitochondrial respiration, limiting protein synthesis. We identify GLUT1 as a critical metabolic player defining the germinal center response and humoral immunity.
CRIS-Team Scopus Importer:2024-02-23
Keywords: adaptive immune response; antibody-secreting cell; CP: Immunology; CP: Metabolism; glucose transporter type 1; GLUT1; glycolysis; metabolism; mitochondrial respiration; plasma cell; plasmablast

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Metabolic profiling of single cells by exploiting NADH and FAD fluorescence via flow cytometry - Abir, Ariful Haque; Weckwerth, Leonie; Wilhelm, Artur; Thomas, Jana; Reichardt, Clara; Munoz, Luis Enrique; Völkl, Simon; Appelt, Uwe; Mroz, Markus; Niesner, Raluca; Hauser, Anja; Fischer, Rebecca Sophie; et al. (Molecular Metabolism, 2024)
Objective: The metabolism of different cells within the same microenvironment can differ and dictate physiological or pathological adaptions. Current single-cell analysis methods of metabolism are not label-free. Methods: The study introduces a label-free, live-cell analysis method assessing endogenous fluorescence of NAD(P)H and FAD in surface-stained cells by flow cytometry. Results: OxPhos inhibition, mitochondrial uncoupling, glucose exposure, genetic inactivation of glucose uptake and mitochondrial respiration alter the optical redox ratios of FAD and NAD(P)H as measured by flow cytometry. Those alterations correlate strongly with measurements obtained by extracellular flux analysis. Consequently, metabolically distinct live B-cell populations can be resolved, showing that human memory B-cells from peripheral blood exhibit a higher glycolytic flexibility than naïve B cells. Moreover, the comparison of blood-derived B- and T-lymphocytes from healthy donors and rheumatoid arthritis patients unleashes rheumatoid arthritis-associated metabolic traits in human naïve and memory B-lymphocytes. Conclusions: Taken together, these data show that the optical redox ratio can depict metabolic differences in distinct cell populations by flow cytometry.
CRIS-Team Scopus Importer:2024-07-19
Keywords: FAD; Flow cytometry; Fluorescence; Metabolism; NADH; Real-time

miR-148a controls metabolic programming and survival of mature CD19-negative plasma cells in mice - Pracht, Katharina; Meinzinger, Julia; Schulz, Sebastian; Daum, Patrick; Corte-Real, Joana; Hauke, Manuela; Roth, Eduard; Kindermann, Dorothea; Mielenz, Dirk; Schuh, Wolfgang; Wittmann, Jürgen; Jäck, Hans-Martin (European Journal of Immunology, 2021)
Long-lived antibody-secreting plasma cells are essential to establish humoral memory against pathogens. While a regulatory transcription factor network has been established in plasma cell differentiation, the regulatory role of miRNAs remains enigmatic. We have recently identified miR-148a as the most abundant miRNA in primary mouse and human plasma cells. To determine whether this plasma cell signature miRNA controls the in vivo development of B cells into long-lived plasma cells, we established mice with genomic, conditional, and inducible deletions of miR-148a. The analysis of miR-148a-deficient mice revealed reduced serum Ig, decreased numbers of newly formed plasmablasts and reduced CD19-negative, CD93-positive long-lived plasma cells. Transcriptome and metabolic analysis revealed an impaired glucose uptake, a reduced oxidative phosphorylation-based energy metabolism, and an altered abundance of homing receptors CXCR3 (increase) and CXCR4 (reduction) in miR-148a-deficient plasma cells. These findings support the role of miR-148a as a positive regulator of the maintenance of long-lived plasma cells.
CRIS-Team Scopus Importer:2021-02-05
Keywords: CXC receptors; Glut-1; miR-148a; Oxidative phosphorylation; Plasma cells

miR-148a promotes plasma cell differentiation and targets the germinal center transcription factors Mitf and Bach2 - Porstner, Martina; Winkelmann, Rebecca; Daum, Patrick; Schmid, Julia; Pracht, Katharina; Corte-Real, Joana; Schreiber, Sandra; Haftmann, Claudia; Brandl, Andreas; Mashreghi, Mir-Farzin; Gelse, Kolja; Hauke, Manuela; et al. (European Journal of Immunology, 2015)
B cells undergo affinity maturation and class switch recombination of their immunoglobulin receptors during a germinal center (GC) reaction, before they differentiate into long-lived antibody-secreting plasma cells (PCs). Transcription factors such as Bach2 and Mitf are essential during this process, as they delay premature differentiation of GC B cells by repressing Blimp-1 and IRF4, two transcription factors required for terminal PC differentiation. Therefore, Bach2 and Mitf expression must be attenuated in activated B cells to allow terminal PC differentiation, but the precise mechanism remains enigmatic. Here, we provide evidence that miR-148a, a small noncoding microRNA, fosters PC differentiation and survival. Next-generation sequencing revealed that miR-148a is the most abundant microRNA in primary human and murine PCs, and its expression is upregulated in activated murine B cells and coincides with Blimp-1 synthesis. miR-148a targets Bach2, Mitf and proapoptotic factors such as PTEN and Bim. When prematurely expressed, miR-148a promotes the differentiation and survival of plasmablasts and reduces frequencies of IgG1(+) cells in primary B-cell cultures. In summary, we propose that miR-148a is a new player in the regulatory network controlling terminal PC differentiation and could, therefore, be a therapeutic target for interfering with PC differentiation and survival.
EVALuna2:13632

miRNA meets plasma cells "How tiny RNAs control antibody responses" - Meinzinger, Julia; Jäck, Hans-Martin; Pracht, Katharina (Clinical Immunology, 2018)
We review the importance of small non-coding microRNAs for the generation of germinal center B cells and their differentiation in antibody-secreting plasma cells. In the last part, we briefly elucidate the role of microRNAs in some plasma cell disorders.
EVALuna2:36046

The intestine: A highly dynamic microenvironment for IgA plasma cells - Pracht, Katharina; Wittner, Jens; Kagerer, Fritz; Jäck, Hans-Martin; Schuh, Wolfgang (Frontiers in Immunology, 2023)
To achieve longevity, IgA plasma cells require a sophisticated anatomical microenvironment that provides cytokines, cell-cell contacts, and nutrients as well as metabolites. The intestinal epithelium harbors cells with distinct functions and represents an important defense line. Anti-microbial peptide-producing paneth cells, mucus-secreting goblet cells and antigen-transporting microfold (M) cells cooperate to build a protective barrier against pathogens. In addition, intestinal epithelial cells are instrumental in the transcytosis of IgA to the gut lumen, and support plasma cell survival by producing the cytokines APRIL and BAFF. Moreover, nutrients are sensed through specialized receptors such as the aryl hydrocarbon receptor (AhR) by both, intestinal epithelial cells and immune cells. However, the intestinal epithelium is highly dynamic with a high cellular turn-over rate and exposure to changing microbiota and nutritional factors. In this review, we discuss the spatial interplay of the intestinal epithelium with plasma cells and its potential contribution to IgA plasma cell generation, homing, and longevity. Moreover, we describe the impact of nutritional AhR ligands on intestinal epithelial cell-IgA plasma cell interaction. Finally, we introduce spatial transcriptomics as a new technology to address open questions in intestinal IgA plasma cell biology.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Aryl hydrocarbon (Ah) receptor; IgA; IgA plasma cells; intestinal epithelial barrier; intestinal epithelial cell; plasma cell; survival niche

The microRNA processing subunit DGCR8 is required for a T cell-dependent germinal center response - Daum, Patrick; Ottmann, Shannon; Meinzinger, Julia; Schulz, Sebastian; Corte-Real, Joana; Hauke, Manuela; Roth, Edith; Schuh, Wolfgang; Mielenz, Dirk; Jäck, Hans-Martin; Pracht, Katharina (Frontiers in Immunology, 2022)
We have previously shown that the microRNA (miRNA) processor complex consisting of the RNAse Drosha and the DiGeorge Critical Region (DGCR) 8 protein is essential for B cell maturation. To determine whether miRNA processing is required to initiate T cell-mediated antibody responses, we deleted DGCR8 in maturing B2 cells by crossing a mouse with loxP-flanked DGCR8 alleles with a CD23-Cre mouse. As expected, non-immunized mice showed reduced numbers of mature B2 cells and IgG-secreting cells and diminished serum IgG titers. In accordance, germinal centers and antigen-specific IgG-secreting cells were absent in mice immunized with T-dependent antigens. Therefore, DGCR8 is required to mount an efficient T-dependent antibody response. However, DGCR8 deletion in B1 cells was incomplete, resulting in unaltered B1 cell numbers and normal IgM and IgA titers in DGCR8-knock-out mice. Therefore, this mouse model could be used to analyze B1 responses in the absence of functional B2 cells.
CRIS-Team WoS Importer:2023-01-27

The microRNA processing subunit DGCR8 is required for immune response and germinal center formation - Daum, Patrick; Meinzinger, Julia; Pracht, Katharina; Corte-Real, Joana; Wittmann, Jürgen; Jäck, Hans-Martin (2017)
EVALuna2:13656

The role of glucose transporter type 1 in plasma cells - Bierling, Theresa; Gumann, Amelie; Van Schie, Karin; Wichert, Magdalena; Hauke, Manuela; Wittner, Jens; Schuh, Wolfgang; Toes, Rene E. M.; Jäck, Hans-Martin; Pracht, Katharina (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

The role of the miR-148/-152 family in physiology and disease - Friedrich, Michael; Pracht, Katharina; Mashreghi, Mir-Farzin; Jäck, Hans-Martin; Radbruch, Andreas; Seliger, Barbara (European Journal of Immunology, 2017)
MicroRNAs (miRNAs) are endogenously encoded 22 nt small non-coding RNAs. They function as key players of many cellular processes by base pairing with target mRNAs and thereby impairing gene expression at the post-transcriptional level. Recent findings demonstrate a critical role of many miRNAs in immune cell differentiation and immune responses, which is also associated with the development and progression of many tumor and non-tumor diseases. Here we review the multifaceted miRNA-148/-152 family members consisting of miR-148a, miR-148b and miR-152. Next to regulation mechanisms that control the expression of this miRNA family, we will focus on (i) the role of miR-148a in regulating B and T lymphocyte function and its role in associated diseases and (ii) the importance of miR-148/-152 family members for cancer initiation, tumor growth and metastasis formation. In addition, this review aims to highlight some selected targets of the miRNA-148/-152 family members, which are involved in the biology of cancer and maintenance of epigenetic patterns. In conclusion, members of the miR-148/-152 family might represent prognostic markers and/or potential therapeutic targets for treatment of autoimmune disorders, chronic inflammatory diseases and multiple types of cancer.
EVALuna2:13649